Design and Implementation of an Arduino-Based Smart Dam for Automated Water Management (Comprehensive Journal of Science, 2025)
This research explores the design and realization of a smart dam model controlled by Arduino technology to demonstrate modern approaches to water resource management. The system integrates sensors, actuators, and programmed logic to monitor water levels, regulate flow, and prevent overflow through automated gate control. The project emphasizes how low-cost microcontroller platforms can effectively replicate essential hydraulic functions and support real-time decision-making. The results confirm that such systems can enhance safety, efficiency, and automation in dam operations while offering an affordable platform for experimentation and learning. The study further highlights the educational and research potential of microcontroller-based simulations in bridging theoretical knowledge and practical engineering applications. Although the model operates on a reduced scale, it establishes a valuable foundation for future developments in smart dam systems incorporating Internet of Things (IoT) connectivity, renewable energy integration, and predictive control algorithms. Overall, the work illustrates how digital technologies can transform traditional hydraulic infrastructure into intelligent, adaptive, and sustainable systems for the future.
Keywords: Smart Dam, Arduino, Automation, Water Resource Management, IoT, Sensors, Hydraulic Control, Sustainable Engineering, Digital Infrastructure.